The new dimensions of university-business partnerships - Leszek Kwieciński; Agnieszka Anna Młodzińska-Granek (Jesuit University Ignatianum in Krakow, 2019)
RESEARCH OBJECTIVE: The goal of the article is to identify the most significant factors that influence the general trends towards the new dimension of university-business partnerships. THE RESEARCH PROBLEM AND METHODS: The authors state that modernization processes are essential for social development based on two paradigms: the new paradigm of development policy and the knowledge-based economy paradigm. Authors based their assumptions on the rational choice theory, as well as network institutionalism. The preliminary results of the research were based on 23 individual in-depth interviews with representatives of research institutions, universities and entrepreneurs' associations, in four cities in Poland (Cracow, Poznan, Warsaw, Wroclaw). THE PROCESS OF ARGUMENTATION: The new goal of development policy is not only the growth of GDP per capita, but also the raise of living standards. Many of the premises are planted in the modern understanding of global economy, based on knowledge-based economy paradigm, according to which the key ability is to implement research into service and production processes (Błaszczyk et al., p. 70), and university-business partnerships might be the right instrument to achieve that to a greater extent. RESEARCH RESULTS: On the basis of the preliminary research results presented in the article the authors have come to the conclusions that there are three specific levels, within which processes of social change take place, in case of university-business partnerships: 1. culture/customs, 2. legal regulations, 3. access to financial support. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The processes of social change in the context of the new paradigm of development policy have already started - there is a significant need of each of the actors to undertake cooperation, as it is a prerequisite of innovative growth. However, the conditions to start it are not yet sufficiently developed. Hence, there is a strong recommendation that the course of development policy was strongly based on the creation of improved conditions for cooperation.